Water status diagnosis in greenhouse drip-irrigated tomato and celery using leaf turgor dynamics and machine learning - Xu, Quanyue; Chen, Ruixia; Li, Xufeng; Wu, Hongxiang; Ma, Juanjuan; Zheng, Lijian (Frontiers in Plant Science, 2026)
IntroductionAccurate crop water status monitoring is crucial for optimized irrigation in controlled environments, but traditional approaches relying on damaging measurements or sporadic sampling frequently restrict real-time evaluation.MethodsThis study explored the non-invasive leaf patch clamp pressure (LPCP) probe to evaluate the water status of drip-irrigated tomato and celery. Leaf turgor dynamics analysis enabled the characterization of the LPCP probe’s output parameter (Pp) and its environmental drivers, and the development of predictive machine learning models.ResultsThe results indicated that diurnal patterns of Pp in drip-irrigated tomato and celery exhibited two distinct states: State I (unimodal) and State II (troughed), corresponding to moisture conditions with no or mild stress, and severe stress, respectively. The soil water content (SWC) thresholds for State I were set at SWC > 20% (tomato) and SWC > 19% (celery), whereas those for State II were set at SWC < 18% (tomato) and SWC < 16% (celery). For State I, Pp was positively associated with solar radiation but negatively associated with SWC (in tomato) and wind speed (in celery). For State II, the associations between Pp and environmental parameters were less than those in State I. Interestingly, compared to full irrigation, non-full irrigation treatments not only showed a higher proportion of State II but also resulted in an increase in both Pp,max and Pp,min by 15.39%–138.39% in tomato and 3.44%–94.02% in celery. These analytical results yielded four model parameter combinations based on the inclusion of SWC and the management of distinct Pp states. The prediction model that integrated Combination 4 (substate Pp prediction based on meteorological factors and SWC) with the random forest approach exhibited the highest accuracy (R2 = 0.995, MSE = 2.419, RMSE = 1.540, and MAE = 0.531), with SWC identified as its key feature parameter.DiscussionThese findings provide a scientific foundation for optimizing the precision irrigation of greenhouse vegetables in drip systems.